2019
DOI: 10.1016/j.ijbiomac.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequencing reveals a key role for the long non-coding RNA MIAT in regulating neuroblastoma and glioblastoma cell fate

Abstract: Myocardial Infraction Associated Transcript (MIAT) is a subnuclear lncRNA that interferes with alternative splicing and is associated with increased risk of various heart conditions and nervous system tumours. The current study aims to elucidate the role of MIAT in cell survival, apoptosis and migration in neuroblastoma and glioblastoma multiforme. To this end, MIAT was silenced by MIAT-specific siRNAs in neuroblastoma and glioblastoma cell lines, and RNA sequencing together with a series of functional assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 55 publications
(33 reference statements)
1
35
1
Order By: Relevance
“…CASC15‐S has already been found to be a tumor suppressor in NB as mentioned above, 20 which is consistent with our findings. MIAT (Myocardial Infarction Associated Transcript) has recently been found to possess tumor‐promoting properties in glioblastoma and NB, which is contrary to our findings and need further investigation 33 . The rest of the other lncRNAs identified in this study have not been reported to be associated with NB before.…”
Section: Discussioncontrasting
confidence: 99%
“…CASC15‐S has already been found to be a tumor suppressor in NB as mentioned above, 20 which is consistent with our findings. MIAT (Myocardial Infarction Associated Transcript) has recently been found to possess tumor‐promoting properties in glioblastoma and NB, which is contrary to our findings and need further investigation 33 . The rest of the other lncRNAs identified in this study have not been reported to be associated with NB before.…”
Section: Discussioncontrasting
confidence: 99%
“…Knockdown of lncRNA myocardial infarction associated transcript (MIAT) reduces cell growth and migration, and enhances apoptosis in NB cell line when compared with that in control [386]. Atmadibrata et al reported that linc00467 can increase cell viability and reduce apoptosis and cell cycle arrest in NB cells via suppressing DKK1 expression [387].…”
Section: Lncrnas In Neuroblastoma (Nb)mentioning
confidence: 99%
“…Large quantities of studies have highlighted the role of lncRNAs in carcinomas. 5,[14][15][16] SNHG7 has been well-accepted as an oncogenic lncRNA in various carcinomas. 7,[17][18][19] In our study, we found that SNHG7 was upregulated in TC cells.…”
Section: Discussionmentioning
confidence: 99%